Biomassa acumulada, nutrientes, radiação solar e produtividade em um sistema de integração lavoura-pecuária-floresta (ILPF) no Cerrado central - Guimarães, Luanna Elis (2015)
Over the time, there was a renewed interest and growth in the adoption of sustainable production systems. Attemps to integrate agricultural activities, livestock and forestry, in order to increase the efficiency of land use, energy, nutrients and labor. This study had as objective to evaluate: a) a three year CLFS, regarding to litter accumulated biomass and nutrients stock; b) biomass and forage productive of Urochloa brizantha (Stapf) Webster; c) to analyze the behavior of photosynthetically active radiation (PAR), microclimate, being all the evaluations done in two different periods (dry and wet season) in a crop livestock forest system (CLFS) in Cachoeira Dourada county, Goiás. The evaluations were performed in CLFS formed by plants of E. urograndis in the following spacing: 4 (3 X 3 m) + 22 m brachiaria forage crop (U. brizantha (Stapf) Webster.).In a) it was determined six blocks with two treatments - one between plants and between rows of eucalyptus. In each block 10 samples were taken for each treatment. To collect the accumulated litter, a wooden frame (0,25 m x 0,25 m) was used. After drying the material was separated in the following components: leaf, bark/branches and miscellaneous and total weight was obtained. After that, the samples were conducted to lab to analyze nutrients content. The results were 17.9 Mg ha-¹ of litter accumulated biomass. There was no difference among the sampled sites (between rows and between plants) for both biomass and the concentration of nutrients. It can be assured that the largest accumulated biomass was obtained in the dry season, and the most representative accumulated biomass was the leaf component. The macronutrient with the highest accumulation in the evaluated components was calcium (Ca) and micronutrient was the iron (Fe). In B) forage sampling was done at 01, 04, 08 and 12 meters, for each block (total six blocks) using two transects of 75 meters equidistant. A wooden frame (0,25m²) was used (0,25m²) and all above ground fodder was removed. After that, dry matter (DM) content was determined and also the calculation of the forage production. The results showed DM differences in wet season. The analysis of variance carried out (p> 0.05) was noted that every meter that the sample was advancing towards the center of the pasture, increased 58% in productivity. It is possible to conclude that the higher productivity occurs in wet season. Highest production (DM) occurred in samples collected at 8 and 12 meters away from the hedgerow. In C) to collect the photon flux density - PFD (μmol.m-2.s-1) two quanta sensors were used (LI-250 A, Li-color Inc., USA), in photosynthetically active radiation - PAR. Data collection was done in each hour, starting at 9:45 and ending at 17:45, and also collected the control to full sun, and other collections in: (1 in the center of the row of trees, 2 – at 5 m of hedgerow 3 –at 10m of hedgerow 4- at 15m of hedgerow ), in each point 4 replications were obtained. A mini-weather station (Windmate WM-300) was used for measuring, in each hour, temperature, wind speed and relative humidity. The results showed that there were differences among the chosen points, with point 10 and 15 meters with most receiving range (PAR). The weather evaluation showed long retaining humidity in the environment, and with mild temperatures, besides the wind force of the breaking by eucalyptus trees present in CLFS. In conclusion, CLFS shows a differential microclimate and also, establish patterns of PAR increase, in this study, 56% for each meter towards to forage center.